Implementation of covid-19 vaccination in the United Kingdom. (29th September 2022) - Majeed, Azeem; Pollock, Katrina; Hodes, Simon; Papaluca, Marisa
Abstract : Decisions about approving covid-19 vaccines and strategies for their use in the UK must be rapid and transparent, say Azeem Majeed and colleagues, and a sustainable infrastructure should be put in place for delivering covid-19 vaccines to the public